Effects of Pneumo-guard H® and Vitamin E on gain and health of stockers purchased as steers and bulls - Brazle, F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pneumo-Guard H® and injectable Vitamin E did not improve cattle gain or reduce treatments required per animal during a 29-day receiving trial. Stockers purchased as steers gained faster (P<.001) and required fewer (P<.001) treatments per animal than bulls castrated on arrival.
Keywords: Beef; Pneumo-guard H®; Vitamin E; Stockers